Wajaran Penggunaan data korpus dalam penulisan ilmiah: Dimensi baharu sukatan pelajaran Bahasa Melayu Sijil Tinggi Pelajaran Malaysia(STPM) (The Use of Data Corpus in Academic Writing: A New Dimension in STPM Malay Language Syllibus) - Isam, Hishamudin; Ahmad, Faizah; Abd Mutalib, Mashetoh (Fakulti Pendidikan, UKM, 2014)
The initiation of syllabus drafting for the Malay Language subject in the year 2012 by the Ministry of Education aims at replacing its previous account which has been used since the Malaysian Higher School Certificate in 2000.The drafting, which also acts as a double-barrelled strategy aspires to produce students with equal knowledge of cognitive, manipulative and soft skills.The search for the new Malay language syllabus has also presented the researchers with various advantages that can be exploited by various parties, particularly the teachers and students. Thus this conceptual paperwork seeks to analyse the reformulated content of the syllabus whilst examines possible scopes and areas to be exercised and manipulated by the Form Six Malay Language teachers with respect to the proliferation's and accomplishments of studies in the field of language and linguistics to be associated with the needs of the new syllabus. Based on the new components introduced in the syllabus, such as the introduction of academic writing component on a termly basis, it is assumed that the positive prospect of having Form Six’s qualification comparable to pre-university program offered by private institutions, and the elevation of STPM examination status according to the needs of teaching and learning orientations at colleges and universities are possible to be realised.